Interns perception towards pharmacology during clinical postings at RIMS, Raichur, India - Gavimath, Neeta T.; Chavan, Vasant R.; Dixit, Rohit (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Every medical graduate must have the intention to prescribe rationally. It is pharmacology which teaches rational of prescribing of drug in undergraduate medical course. Therefore, many eminent medical educationists believe that pharmacology is the most essential part of the medical curriculum. Medical graduates join as interns in their respective teaching hospital immediately after graduation. Although interns work is usually under the supervision of a senior consultant but there are occasions, when they need to make their own decision. Internship is the intermediate period between under-graduation and general practice. The dexterity of health professional relies upon prescribing practices. Clinical pharmacology and therapeutics (CPT) is a crucial discipline for interns to acquire safe and rational prescription of drugs. This study was conducted with the intention to provide some light about the knowledge of pharmacology among the interns in RIMS Hospital Raichur, Karnataka. Methods: The study was done on interns of RIMS, Raichur. It was a descriptive questionnaire-based prospective study. A structured questionnaire modified from the work of Oshikoya et al, was used in the study which included four major categories namely basic demographic information, undergraduate CPT teaching, experience of adverse drug reaction (ADR) and any deficiency in the under-graduate CPT teaching. Results: Out of these 107 participants 54 (42%) rated pharmacology knowledge is good, while another 53(40%) had average understanding. As high as 80% (85) intern population feel that undergraduate training has prepared them to prescribe safely. 45 (41%) interns have already observed cases of adverse drug reactions in their short active clinical life. Conclusions: The present study has identified that pharmacology and therapeutics course curriculum is not enough to produce safe prescribers.